Perception of dental students on risk factors of musculoskeletal disorders - Botta, A. C.; Presoto, C. D.; Wajngarten, D.; Campos, J. A.D.B.; Garcia, P. P.N.S. (My University, 2018)
Objective: To evaluate the validity and reliability of the Job Factors Questionnaire, and the influence of gender, academic level and pain/discomfort on dental students' perception regarding risk factors of musculoskeletal disorders. Methods: One hundred forty-five dental students from Stony Brook School of Dental Medicine participated voluntarily in this study. The survey was organised in two sections: (i) Job Factors Questionnaire with 15 items that evaluated students' perceptions about job/study environmental risk factors and their potential contribution to musculoskeletal disorders. The tri-factorial structure (repetitiveness, work posture and external factors) was used; (ii) Part of the Nordic Questionnaire with questions referring to 9 body areas: Neck, shoulders, upper back, elbows, lower back, wrists/hands, hips, knees and ankles/feet. Students answered if they have had a job-related pain/discomfort in any of these body areas in the previous 12 months. The data were evaluated statistically by confirmatory factor analysis, convergent and discriminant validities, internal consistency and Z-test (α = .05). Results: The tri-factorial structure was considered valid and reliable for the sample after excluding item 8 and inserting correlations between items 11 and 12, and between 14 and 15. The academic level presented a significant effect on the factors Work Posture (P = .02) and External Factors (P = .01). Most of the students reported pain in their neck (73.79%), lower back (62.06%) and shoulders (53.10%) in the previous 12 months. Conclusion: The Work Posture and External Factors were influenced only by academic level. The lower the students' academic level, the higher their perception for both factors of musculoskeletal disorders.
Keywords: Dental students; Ergonomics; Health education; Musculoskeletal disorders; Risk factors